19. SOME RELATED FACTORS TO THE TREATMENT PROGNOSIS FOR TOTAL HIP REPLACEMENT SURGERY IN PATIENTS WITH AVASCULAR NECROSIS OF THE FEMORAL HEAD AT HA TINH TTH GENERAL HOSPITAL (2022-2023) (Vietnam Journal of Community Medicine, 2024)
Objective: Determine factors related to the results of total hip replacement in patients with aseptic necrosis of the femoral head.Method: Designed descriptive research method with analysis (univariate and multivariate correlation analysis).Results: Analyzing factors related to prognosis of treatment results for aseptic degeneration of the femoral head include: age group, gender, occupation, underlying disease, pain duration, osteoporosis status, anemia, use of some stimulants such as alcohol, cigarettes...Multivariate correlation analysis results show that related factors include: age group ≥ 55 (OR = 2.198; 95%CI from 1.091-4.429; p < 0.05); limb shortening (OR = 3.141; 95%CI from 1.564-6.308; p < 0.01); prolonged corticosteroid use (OR = 3.053; 95%CI from 1.306-7.141; p < 0.01); have underlying disease (OR = 2.391; 95%CI from 1.153-4.959; p < 0.05).Conclusion: The factors most related to the results of treatment for aseptic degeneration of the femoral head are age group ≥ 55, limb shortening, prolonged use of corticosteroids, and underlying disease.
Keywords: Aseptic degeneration of the femoral head; hip replacement